Split-hand/feet malformation in three tamilian families and review of the reports from India - Amalnath, S. Deepak (Medknow Publications & Media Pvt Ltd, 2014)
Split-hand/foot malformation (SHFM) is a rare condition which can be either syndromic or nonsyndromic. We report three unrelated pedigrees, one with autosomal dominant (AD) inheritance and the other two with autosomal recessive (AR) pattern. We also briefly review the published reports from India.